Paddy Field Pawn Practices in Rural Communities: A Maqashid Sharia Perspective on Potential Economic Exploitation - Mazidurrahman; Saifuddin (Anjasmoro: Islamic Interdisciplinary Journal, 2026)
Paddy field pawn (rahn) practices remain a common form of traditional financing among rural farmers due to limited access to formal financial institutions. In Montorna Village, Pasongsongan District, Sumenep Regency, this practice is commonly carried out through a mechanism in which the lender (murtahin) gains control over the pledged land and often enjoys the entire harvest yield without reducing the principal debt owed by the borrower (rahin). Such conditions have the potential to create economic exploitation because the contract is implemented without a clear time limit, while the benefits received by the murtahin may exceed the value of the original loan. This study aims to analyze the practice of paddy field pawning and examine it from the perspective of maqashid sharia. The research employed a qualitative approach with a case study design, utilizing interviews, observations, and documentation as data collection techniques. The findings indicate that the existing practice does not fully fulfill the principles of hifz al-mal (protection of wealth) and hifz al-nafs (protection of human welfare). Therefore, improvements are required in the contractual arrangement to ensure greater fairness, transparency, and compliance with the principles of Islamic economics.